PENGARUH PENGGUNAAN TEKNOLOGI IRIGASI TETES TERHADAP PENDAPATAN USAHATANI CABAI DI KECAMATAN WOLOWAE KABUPATEN NAGEKEO - Ramot, Karolina; Surayasa, Made Tusan; Malle, Imanuel (Undana Press, 2024)
The constraint faced by farmers in Wolowae Sub-district is the lack of water availability during the dry season. One of the efforts to increase agricultural productivity in drylands is to develop water-saving irrigation technology (drip irrigation), on land with limited water sources. Adopting an agricultural technology will certainly require additional costs in the production process. This study aims to determine: (1) the productivity of chili farming before and after using drip irrigation technology (2) the difference in chili farming income before and after using drip irrigation technology and (3) the feasibility of chili farming that applies drip irrigation technology. This research was conducted in Anakoli Village and Totomala Village, Wolowae District, Nagekeo Regency in May and June 2023. The research location was determined by purposive sampling. The determination of the sample in this study was carried out using the simple random sampling method with a sample size of 78 people determined using the Isaac and Michael formula. The data collection method in this study is a survey method by collecting primary data and secondary data. The collected data were analyzed descriptively and a simple statistical test was carried out, namely the Paired sample T-test (t test). The results showed that (1) the productivity of chili farms after using drip irrigation technology is higher than before using drip irrigation technology (4 tons / ha) (2) there is a significant difference in income on chili farms before and after using drip irrigation technology (0.006 <0.05) and (3) R / C ratio shows that the value of R / C> 1 so that chili farms using drip irrigation technology are feasible to cultivate R / C (5.03).